Non-immune Hydrops Fetalis Secondary to Nuchal Cystic Hygroma: Prenatal Detection and Postnatal Evaluation of 5 Cases - Eserdağ, Süleyman; Zülfikaroğlu, Ebru; Tuncay, Görkem; Ceylaner, Serdar; Danışman, Nuri (Gynecology Obstetrics & Reproductive Medicine, 2006)
Non-immune hydrops fetalis secondary to nuchal cystic hygroma is a lethal congenital malformation, resulting from the lack of communication between the jugular venous system and the cervical lymphatic vessels in the nuchal region. Identification of these abnormalities by sonography is not important for the management, but also for genetic counseling. In this paper, we report 5 cases of severe hydropic fetuses secondary to nuchal cystic hygroma, prospectively detected during sonographic examination between January 2002 and January 2003 at our hospital outpatient clinic.